2014
DOI: 10.1061/(asce)gt.1943-5606.0000948
|View full text |Cite
|
Sign up to set email alerts
|

Ground Movements due to Shallow Tunnels in Soft Ground. I: Analytical Solutions

Abstract: This paper presents simplified closed-form analytical solutions that can be used to interpret and predict ground movements caused by shallow tunneling in soft ground conditions. These solutions offer a more comprehensive framework for understanding the distribution of ground movements than widely used empirical functions. Analytical solutions for the displacement field within the ground mass are obtained for two basic modes of deformation corresponding to uniform convergence and ovalization at the wall of a ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 19 publications
0
65
0
Order By: Relevance
“…Mechanized tunneling is a complex engineering problem involving various processes such as consequential excavation, grouting and lining installation [8]. Kasper and Meschke [9] presented a 3D finite element model to take into account all relevant components of the construction process (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanized tunneling is a complex engineering problem involving various processes such as consequential excavation, grouting and lining installation [8]. Kasper and Meschke [9] presented a 3D finite element model to take into account all relevant components of the construction process (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mogi 1958 with a small typo, Yoshikawa 1961), underground tunnels when constructed (see e.g. Verruijt 1996;Zymnis et al 2013;Pinto & Whittle 2014) and underground cavities that collapse. For relatively simple cavity (or reservoir) geometries and boundary conditions inside uniform elastic half-spaces, analytical solutions for rock mass and ground surface displacements exist (see e.g.…”
Section: P R E V I O U S At T E M P T S T O M O D E L L I N G P Ro D mentioning
confidence: 99%
“…16,17 There are many researches on the influencing factors affecting the ground movement during tunnel excavation. Pinto and Whittle, 18 Pinto et al 19 defined the tunnel overburden as a significant parameter that governs the tunneling induced ground movement in their analytical solution, which was validated on the basis of real tunneling projects. Another study conducted by Franzius et al 20 demonstrated the influence of K 0 on ground surface movements resulting from tunnel excavation.…”
Section: Introductionmentioning
confidence: 99%